The system development of fuzzy standards of network parameters - Корченко, Анна Олександрівна (Ukrainian Information Security Research Journal, 2013)
Based on the well-known anomaly detection techniques caused by the cyber —attacks, it was developed an appropriate system which requires the implementation of fuzzy standards focused on the measurement of current parameter value of the network traffic in order to identify suspicious activity in the Knvironment. To solve this task it was suggested a new structural decision of the corresponding system, consisting of the register of standards, attacks and parameters, as well as blocks of switching parameters, linking the attack to the parameter, die development of set of terms, the development of standards, register of standards and the processor of standards visualization. This development can be implemented through the software or firmware, hardware and focused on die measurement of current values of parameters in the network traffic in order to identify an abnormal condition.